The effects of carbohydrate, caffeine, L-Menthol, and combination (carbohydrate + caffeine + L-Menthol) mouth rinsing on intense intermittent exercise performance / Nur Irdina Farhani ... [et al.]. - Farhani, Nur Irdina; Linoby, Adam; Shah, Muhammad Azizi; Mohd Dan, Azwa Suraya; Kamaruddin, Harris Kamal; Nugraha, Reshandi; Machado, Marco (2024)
Mouth rinsing with solutions containing carbohydrates (CHO), caffeine (CAF) and L-menthol (MEN), has been suggested to enhance exercise performance by providing ergogenic effects through various mechanisms such as oral sensing and improved perceptual responses. However, the individual and combined impacts of these substances on high-intensity intermittent exercise remain unclear. This study aimed to address this research gap by examining the effects of CHO, CAF, MEN, and their combination (CHO+CAF+MEN; MIX) on exercise performance, heart rate (HR), and rating of perceived exertion (RPE) in recreationally active young men. Eighteen participants (mean ± SD: (mean ± SD: age 22 ± 2 years, body mass 62 ± 7 kg, height 168 ± 0.06 cm, VO2 max 48 ± 3 mL/kg/min) underwent a randomized, double-blind, placebo-controlled crossover study involving six trials with different mouth rinse conditions. Results indicated that CHO mouth rinsing significantly enhanced performance in the Yo-Yo intermittent recovery level 1 (Yo-Yo IR1) test compared to placebo (PLA) and control (CON) (CHO: 1440 ± 288 m vs. PLA: 1383 ± 282 m, and vs. CON: 1373 ± 282 m; both p < 0.05), but not when compared to other rinses. RPE values for the CHO condition were significantly lower than PLA and CON during the Yo-Yo IR1 tests (p < 0.05). No significant differences in HR were observed among the conditions. These findings suggest that CHO mouth rinsing can enhance intermittent exercise performance, possibly by reducing perceptual effort, offering a practical strategy for athletes and active individuals.